The supernatural world of the Quechuas of southern Peru, through the Qotobamba Community - Núñez Del Prado Béjar, Juan Víctor (1970)
The present work has been fundamentally carried out based on the materials raised in the community of Qotabamba, in different periods: The first, in two months, in the year 1964, as part of the research work for the project of Studies of Changes in Peoples Peruvians, sponsored by the Institute of Peruvian Studies; the second, a similar period between February and March 1966 under the same auspices in carrying out the second stage of basic studies, corresponding to the community of Qotabamba and as an integral part of the aforementioned Project; the third, during the months of October and November 1968, in compliance with the curricular requirement in the field work corresponding to the Ethnology Research and Folklore Research courses, of the Department of Anthropology of the National University of Cuzco. During this period Gloria Miranda V., Rina Cornejo, Alberto Vera A. and Augusto Salizar S. worked in the neighboring communities of Mask'a and Kuyo Chico as 5th year Anthropology students, using some of their data field.